Pelatihan Redesain Sistem Penjajaran Rekam Medis di Klinik Pratama Aisyiyah Siti Khotijah Salam Kabupaten Magelang - Eniyati Eniyati; Kori Puspita Ningsih; Zakharias Kurnia Purbobinuko (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Good medical record management will affect the quality of health services. A good medical record must be qualified: accurate, complete, contain clear data, contain new information data that shows the patient's current status, informative, and accountable. Medical record management greatly affects the quality of health services. Storage room (filing) where medical record documents are stored, because medical records are confidential and have legal aspects, physical security is the responsibility of health facilities Alignment is a form of medical record management that functions as a sequencing to put medical records on storage shelves so that they can be found again when needed by patients, medical personnel or other needs. The alignment used is like an alphabetic system or based on numerical systems such as the straight numerical system (straight Numerical System), middle number system (Middle Digit Filing System) and final number system (Terminal Digit Filing System). Aisyiyah Siti Khotijah Salam primary clinic Magelang Regency is a primary clinic with health workers consisting of general practitioners, specialists, midwives, nurses and administrative personnel. For medical recording personnel themselves, it is not adequate, so there are problems related to medical record management. In this community service activity, training was carried out related to the alignment of medical record files, previously participants were given material related to the alignment of medical records. The result of this study is the improvement of the alignment system at Pratama Aisyiyah Siti Khotijah Salam Magelang Clinic.